Peningkatan Kompetensi Pustakawan di Perpustakaan SMK Kesehatan Sadewa Melalui Pendidikan dan Pelatihan oleh Ikatan Pustakawan Indonesia (IPI) Daerah Istimewa Yogyakarta - Ernawati; Nailil Hikmah (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2025)
The research was entitled "Improving Librarian Competence at the Sadewa Health Vocational School Library through Education and Training by the Indonesian Librarians Association (IPI DIY). This study aimed to determine how to improve librarian competency at the Sadewa Health Vocational School Library in Yogyakarta. The data collection method used a qualitative approach with a case study. Data collection techniques included interviews, observation, and documentation. Thematic analysis was used for data analysis. The results and discussion of the data processing revealed that librarian competency at the Sadewa Health Vocational School Library in Yogyakarta can be improved through education and training in the library field. Based on the analysis, the study concluded that the education and training program for school librarians conducted by the Indonesian Librarians Association (IPI) in the Special Region of Yogyakarta played a significant role in improving librarian competency at the Sadewa Health Vocational School Library in Yogyakarta. This competency improvement contributed to the library's success in achieving an A-level accreditation.